Optimization of China’s maize and soy production can ensure feed sufficiency at lower nitrogen and carbon footprints - Liu, Zitong; Ying, Hao; Chen, Mingyou; Bai, Jie; Xue, Yanfang; Yin, Yulong; Batchelor, William D.; Yang, Yi; Bai, Zhaohai; Du, Mingxi; Guo, Yixin; Zhang, Qingsong; et al. (Nature Food, 2021)
China purchases around 66% of the soy that is traded internationally. This strains the global food supply and contributes to greenhouse gas emissions. Here we show that optimizing the maize and soy production of China can improve its self-sufficiency and also alleviate adverse environmental effects. Using data from more than 1,800 counties in China, we estimate the area-weighted yield potential (Ypot) and yield gaps, setting the attainable yield (Yatt) as the yield achieved by the top 10% of producers per county. We also map out county-by-county acreage allocation and calculate the attainable production capacity according to a set of sustainability criteria. Under optimized conditions, China would be able to produce all the maize and 45% of the soy needed by 2035—while reducing nitrogen fertilizer use by 26%, reactive nitrogen loss by 28% and greenhouse gas emissions by 19%—with the same acreage as 2017, our reference year.